2017
DOI: 10.1021/acs.jmedchem.7b00419
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small Molecules as Multi-Toll-like Receptor Agonists with Proinflammatory and Anticancer Activities

Abstract: Therapies based on activation of multiple Toll-like receptors (TLRs) may offer superior therapeutic profiles than that of single TLR activation. To discover new small molecules that could activate multiple TLRs, we performed a cell-based high-throughput screening of a small-molecule library based on TLR3-mediated NF-κB activation. Subsequent structural optimization and counterscreening of other TLRs produced the first small molecule 17e (CU-CPT17e) capable of simultaneously activating TLRs 3, 8, and 9. Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 69 publications
0
40
0
Order By: Relevance
“…The only known agonist for this TLR is poly‐ICLC (and its derivatives), which is being investigated in various clinical trials . The success and ubiquitous nature of poly‐ICLC led to the belief that this was the only realistic possibility for targeting this TLR; however, recent studies have identified other small molecules that can either inhibit or activate TLR3 . These alternatives will not be available for clinical trials for a considerable period of time.…”
Section: Therapeutic Interventions Targeting Tlrsmentioning
confidence: 99%
“…The only known agonist for this TLR is poly‐ICLC (and its derivatives), which is being investigated in various clinical trials . The success and ubiquitous nature of poly‐ICLC led to the belief that this was the only realistic possibility for targeting this TLR; however, recent studies have identified other small molecules that can either inhibit or activate TLR3 . These alternatives will not be available for clinical trials for a considerable period of time.…”
Section: Therapeutic Interventions Targeting Tlrsmentioning
confidence: 99%
“…Recently, the cooperation between TLR7 and NOD2 signaling was demonstrated in response to Candida parapsilosis infection [19] . As part of the evaluation of the interest of the crosstalk between PRR agonists, the combination of multiple agonists in a single molecule showed promising effects in multiple studies [20] , [21] , [22] . Most pathogens enter the body through mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a plethora of synthetic methods has been developed for the preparation of those scaffolds in the past century (Scheme ) . Generally, the synthesis of chroman‐4‐ones could be achieved by intramolecular oxo‐Michael addition of 2'‐hydroxychalcone catalyzed by acids/bases (Scheme a), and condensation cyclization of o ‐hydroxyacetophenones with ketones or aldehydes (Scheme b) . However, those synthetic approaches only led to 2‐substituted and 2,2‐disubstituted chroman‐4‐ones.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Generally, the synthesis of chroman-4-ones could be achieved by intramolecular oxo-Michael addition of 2′hydroxychalcone catalyzed by acids/bases (Scheme 2a), [10][11][12][13][14] and condensation cyclization of o-hydroxyacetophenones with ketones or aldehydes (Scheme 2b). [15][16][17][18] However, those synthetic approaches only led to 2-substituted and 2,2-disubstituted chroman-4-ones. For the synthesis of 3-substituted chroman-4-ones, intramolecular Stetter reaction of alkenyl aldehydes catalyzed by N-heterocyclic carbene (NHC) was found to be an efficient procedure (Scheme 2c).…”
Section: Introductionmentioning
confidence: 99%